Implementation of Realistic Mathematics Approach to Mathematical Critical Thinking Skill - Saputri, Lilis; Fauzi, KMS. Muhammad Amin; Mulyono, Mulyono (Perspektif Pendidikan dan Keguruan, 2025)
This study looks the realistic mathematics approach impacts students' critical thinking skills in mathematics. Using a quantitative method and a one-shot case study design, the research examined the relationship between the independent variable (realistic mathematics approach) and the dependent variable (mathematical critical thinking skills) through simple linear regression. Data were collected from 36 students using a mathematical critical thinking skills test and analyzed statistically. The results showed that the realistic mathematics approach significantly improved students' critical thinking skills. This is demonstrated by the regression equation Y=19,584+0,922X, with an F value of 241.436 and a p-value of 0.000, which is less than 0.05. These findings confirm that applying the realistic mathematics approach influences mathematical critical thinking skills. The study highlights the importance of integrating the realistic mathematics approach into the curriculum and teaching practices to help develop students' critical thinking skills. It also suggests opportunities for future research to explore other factors affecting critical thinking skills and to assess this teaching model in broader settings. These findings aim to inspire the creation of more innovative learning models to enhance mathematics education quality.